2014
DOI: 10.1002/wnan.1324
|View full text |Cite
|
Sign up to set email alerts
|

Toward biosensors for the detection of circulating microRNA as a cancer biomarker: an overview of the challenges and successes

Abstract: Considerable attention has been dedicated to developing feasible point-of-care tests for cancer diagnosis and prognosis. An ideal biomarker for clinical use should be easily assayed with minimally invasive medical procedures but possess high sensitivity and specificity. The role of microRNAs (miRNAs) in the regulation of different cellular processes, the unique altered patterns in cancer patients and presence in body fluids in the stable form, points to their clinical utility as blood-based biomarkers for diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 92 publications
(123 reference statements)
0
51
0
Order By: Relevance
“…Aberrant expression levels of miRNAs have been observed in many solid tumours, including breast cancer (Fu et al, 2011), accounting their dysregulated expression in cancer. In addition, miRNAs are stable in the blood and have high/low expressions that can be correlated to chemo-resistance, (Kong et al, 2010; Tavallaie et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression levels of miRNAs have been observed in many solid tumours, including breast cancer (Fu et al, 2011), accounting their dysregulated expression in cancer. In addition, miRNAs are stable in the blood and have high/low expressions that can be correlated to chemo-resistance, (Kong et al, 2010; Tavallaie et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…20 Using a number of in vitro and in vivo methods, 89 nanodiagnostic devices are able to detect the presence of relevant biomarkers (eg, surface proteins of cancerous cells or circulating tumor DNA) at much lower levels, and potentially are able to measure the presence of target biomarkers at the level of single cells and molecules. 68,90 In addition to point-of-care nanodiagnostic methods that have been developed for a range of cancers, 91,92 point-of-care nanodiagnostics continue to be developed for several other pathologies, including Alzheimer's disease, 20,93 diabetes, 94,95 and a number of viral and bacterial infections.…”
Section: Nanodiagnosticsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that the circulatory miRNAs are noticeably resistant to RNase digestion, non-physiologic pH values, and high temperature. Hence, these miRNAs have been considered as promising biomarker for early cancer detection [89]. …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the technical challenges for the quantitative analysis of miRNA become more complex due to their small size, low abundance, and high sequence similarity. In an effort to resolve the mentioned limitations, biosensor technology was suggested as an alternative method for sensitive, specific and non-invasive miRNA detections in early cancer diagnosis [8]. Biosensors are commonly defined as devices composed of recognition elements interfaced with a transducer, which finally transform a capture process into a detectable output signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation